THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON EMPLOYEES’ SATISFACTION: EVIDENCE FROM COMPANIES IN ROMANIA - Nour LAKISS (Management & Marketing)
The aim of this study is to investigate the impact of corporate social responsibility in terms of its dimensions (environmental, community service, and human resources) on employees’ satisfaction within firms listed on the Bucharest Stock Exchange. Design/methodology/approach: A questionnaire was developed and sent by Google Forms to 84 companies in Romania. Respondents included employees at a higher management level within the selected firms. There were 589 questionnaires who were applicable for analysis. Findings: The outcomes of the study found that there is a positive impact of corporate social responsibility through its selected dimensions on employees’ satisfaction in Romania.